Hyperthermic Intravesical Chemotherapy Shed New Light on Therapy for NMIBC: A Meta-Analysis - Zhao, Gang (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Background: Non-muscle-invasive bladder cancer accounts for the 75% of bladder cancers but with limited kinds of therapies, especially in the situation that the shortage and high failure rate of intravesical bacillus Calmette-Guérin. There is some evidence that hyperthermic intravesical chemotherapy could enhance the effect of normal intravesical chemotherapy and may be the alternative. Method: To verify the effect of hyperthermic intravesical chemotherapy, we searched three databases including PubMed (Medline), Embase, and Cochrane Library for related studies. The main outcome were the OR (odds ratio) and the survival data. The quality of studies was evaluated by two authors independently using Jadad Scale for prospective studies and Newcastle-Ottawa Scale (NOS) for retrospective studies. Result: In total, 1,900 patients were included in the quantitative evaluation. The meta-analysis demonstrated significant difference in recurrence rate (OR = 0.42, 95%CI = 0.25-0.72, p=0.0015) and RFS (HR = 0.69, 95%CI = 0.54-0.88, p=0.0029) between hyperthermic intravesical chemotherapy with control groups (intravesical bacillus Calmette-Guérin and normal intravesical chemotherapy) but no obvious advantage in OS (HR = 0.84, 95%CI = 0.59-1.19, p=0.7805) and PFS (HR = 0.51, 95%CI = 0.06-4.08, p=0.5285). We separately use way of heat, control therapy, solvent, country and study type to conduct the subgroup analysis for recurrence rate and RFS. Conclusion: Hyperthermic intravesical chemotherapy can enhance the effect of normal intravesical chemotherapy and act as the alternative for intravesical bacillus Calmette-Guérin, and more studies are needed for further analyses.